2011
DOI: 10.1111/j.1365-2141.2011.08786.x
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly rituximab, cyclophosphamide, vincristine, non‐pegylated liposome‐encapsulated doxorubicin and prednisone (R‐COMP‐14) in elderly patients with poor‐risk diffuse large B‐cell lymphoma and moderate to high ‘life threat’ impact cardiopathy

Abstract: This Phase II study assessed feasibility and efficacy of a biweekly R-COMP-14 regimen (rituximab, cyclophosphamide, non-pegylated liposome-encapsulated doxorubicin, vincristine and prednisone) in untreated elderly patients with poor-risk diffuse large B-cell lymphoma (DLBCL) and moderate to high ‘life threat’ impact NIA/NCI cardiac comorbidity. A total of 208 courses were delivered, with close cardiac monitoring, to 41 patients (median age: 73 years, range: 62–82; 37% >75 years) at a median interval of 15·6 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…However, cardiac toxicity persisted with 21% of cardiac events, grade 3 to 4 in 4% of cases. A larger study with the same regimen given every 2 weeks showed a 4-year time-to-treatment-failure of only 49% (64). Another study used a reduced dose of nonpegylated liposomal doxorubicin (30 mg/m 2 ) in 35 frail elderly patients and obtained favorable results considering this frail population with little toxicity (69% CR in intention-to-treat analysis and 2-year overall survival of 70%; ref.…”
Section: Patients With a Contraindication To Anthracyclinementioning
confidence: 99%
“…However, cardiac toxicity persisted with 21% of cardiac events, grade 3 to 4 in 4% of cases. A larger study with the same regimen given every 2 weeks showed a 4-year time-to-treatment-failure of only 49% (64). Another study used a reduced dose of nonpegylated liposomal doxorubicin (30 mg/m 2 ) in 35 frail elderly patients and obtained favorable results considering this frail population with little toxicity (69% CR in intention-to-treat analysis and 2-year overall survival of 70%; ref.…”
Section: Patients With a Contraindication To Anthracyclinementioning
confidence: 99%
“…In this case a combination of Rituximab with Ifosfamide, Carboplatine and Etoposide (R-ICE) is frequently used with good results [10]. There are several other published regimens but no formal comparison between them [11][12][13][14].…”
Section: Research Articlementioning
confidence: 99%
“…A number of approaches have been proposed to treat these patients. These include deleting doxorubicin from CHOP-R, substituting mitoxantrone for doxorubicin, substituting liposome-encapsulated doxorubicin, 55 substituting etoposide for doxorubicin, using bendamustine-R, 56 and substituting procarbazine for doxorubicin. 2 The approach that I have adopted was recently reported by the Vancouver group.…”
Section: Patients With Heart Diseasementioning
confidence: 99%